INFLUENCE OF PERCEPTION, PARTICIPATION AND IMPLEMENTATION CORPORATE SOCIAL RESPONSIBILITY PROGRAM OF PT. NUSA HALMAHERA MINERALS ON NORTH HALMAHERA FARMERS' INCOME - Hohary, Yunelfi Musraino; Sunaryanto, Lasmono Tri; Yuliawati, Yuliawati (Agric, 2024)
The agricultural industry is crucial for the national economy's growth, and the government is committed to advancing development policies. However, challenges persist, necessitating collaboration between the private sector, government, and other stakeholders. This study examines the impact of the Corporate Social Responsibility program on farmers' income in North Halmahera Regency. The study was carried out specifically in the districts of Kao Teluk, Malifut, Kao, Kao Barat, and Kao Utara, between December 2022 and March 2023. The data utilized in this study were gathered through interviews and a questionnaire administered to one hundred respondents, specifically farmers who had benefited from the Community Development and Empowerment of Corporate Social Responsibility program and were deliberately selected using a purposive sampling method. The research employed the Structural Equation Model approach for data analysis and processing, utilizing Microsoft Excel and the SmartPLS application version 4. According to the study's findings, farmer participation and perceptions significantly and positively impacted the implementation of the Corporate Social Responsibility program. Similarly, smallholder participation, perceptions, and the execution of the Corporate Social Responsibility program have a substantial and favorable impact on farmers' income. Enhanced farmer participation is directly proportional to improved farmer perception, thereby facilitating the successful execution of the CSR program and guaranteeing favorable outcomes, impacts, and agricultural sustainability-thereby augmenting farmers' incomes.